Persamaan Fokker Planck dan Aplikasinya Dalam Astrofisika - Palupi, Dwi Satya (BERKALA FISIKA, 2010)
Abstract It has been established Fokker-Planck equation to obtain the evolution of particle distribution functions that describe the motion of particles in a fluid that can not be described by the Liouville equation.Â Fokker-Planck equation contains a diffusion component particles and the interaction between the particles will be discussed application of Fokker-Planck equation in astrophysics since the plasma in the form of interstellar space so that there is interaction between the particles making up the plasma. Â  Keywords: Fokker-Planck, plasma, astrophysics